Analysis of heat transfer mechanism in supercritical fluids from the aspect of pool heating - Liu, Minyun; Liu, Shenghui; Xi, Dapeng; Huang, Shanfang; Huang, Yanping (Frontiers in Energy Research, 2023)
For the special phenomena including heat transfer deterioration and enhancement in supercritical fluid heat transfer, existing research still carries inconsistent opinions. Here we start with the analysis of the property changes and carry out new understandings of pseudo-boiling theory. However, more importantly, the essential differences between subcritical boiling and supercritical pseudo-boiling are indicated and the keys are thermodynamic instability and stability. For the isothermal heating cases, pseudo film boiling can be regarded as an extension of near-critical boiling. Moreover, pseudo nucleate boiling only appears in non-isothermal heating cases, which strongly depends on the heater geometry, materials et al. To verify the view, the coupled level-set and volume-of-fluid method are used to simulate the near-critical film boiling of carbon dioxide for a pressure of 7.0 and 7.37 MPa. In comparison, the supercritical cases for a pressure of 7.5 MPa are the natural convections of single-phase fluid with variable physical properties. The numerical results indicate the similar motions of low-density fluids in subcritical and supercritical cases. All these results are consistent with the prior experiments, which provide better understanding of the special features of the supercritical fluid heat transfer.